2013
DOI: 10.19026/rjaset.6.4006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand Association in Psycho-Social and Psycho-Personality Antecedents a Conceptual Model of Conspicuous Consumption among Youth Adult

Abstract: The knowledge of consumers' behavior is considered as an essential key in successful marketing programs. This would appear more when purchasing luxury products, because in Conspicuous consumption, the motives for buying special products originate more in psychic problems of consumers than product's specifications. This study is aimed to examine the consumption behavior of luxury products among the young people (aging from 18 to 35). Thus, we focused on the two fields of brand association and psychological ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
7
2
Order By: Relevance
“…This finding confirms that lifestyle is directly related to the type of goods demanded (Pan, et al, 2014), in addition to the positive emotions that are reinforced by the purchase of this type of product through the perception of the brand and its collective concept (Hume and Mills, 2013). This finding contradicts the assertion that one of the relevant factors is purchasing power due to the impact of the demand created by brands on consumers' perception, psychologically impacting them through the association between well-being and the brand, which is the basis for accessing this type of product through credit lines (Abdolvand and Reihani, 2013). For this reason, the consumer accesses the product, even though doing so implies costs related to financing, which means that the desire to spend is greater than the financial variables involved in the purchase process (McFerran, et al, 2014).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…This finding confirms that lifestyle is directly related to the type of goods demanded (Pan, et al, 2014), in addition to the positive emotions that are reinforced by the purchase of this type of product through the perception of the brand and its collective concept (Hume and Mills, 2013). This finding contradicts the assertion that one of the relevant factors is purchasing power due to the impact of the demand created by brands on consumers' perception, psychologically impacting them through the association between well-being and the brand, which is the basis for accessing this type of product through credit lines (Abdolvand and Reihani, 2013). For this reason, the consumer accesses the product, even though doing so implies costs related to financing, which means that the desire to spend is greater than the financial variables involved in the purchase process (McFerran, et al, 2014).…”
Section: Discussioncontrasting
confidence: 61%
“…Based on the results presented in the previous section and in contrast to the analysis of the documents consulted, it is demonstrated that even when the decision process for purchasing luxury fashion goods is similar in countries with development conditions that are equal to those of Colombia, this process has some variations; the most representative finding is the importance of the brand, whereas social pressure has less relevance in the purchase decision process (Abdolvand and Reihani, 2013). In Bogota, one of the most cosmopolitan cities in the country, a consumption trend that is mostly driven by fashion trends from world-class brands has been generated.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The knowledge of consumers' behavior is considered as an important key in successful marketing programs. Abdolvand and Reihani (2013) examined the consumption behavior of luxury products among the young people and concentrated on the two fields of brand association and psychological antecedents. They reported that two criteria such as brand association and psychological antecedents significantly influenced the consumption behavior of luxury products among the youth.…”
Section: Introductionmentioning
confidence: 99%